Investigating Early Vocabulary Acquisition on 18-24-Month-Old Child: A Study of Vocabulary Spurt and Function Words - Paris, Atika Salman; Rafli, Zainal; Murtadho, Fathiaty; Wang, Huang Yan (Journal of Language and Literature Studies, 2025)
This study investigates vocabulary acquisition and the phenomenon of vocabulary spurt in a 24-month-old child, focusing on the interplay of cognitive abilities, memory, and understanding of word functions. The research aims to answer two primary questions: How do cognitive abilities and memory influence the vocabulary spurt in a 24-month-old child’s vocabulary acquisition? And to what extent does understanding word functions contribute to vocabulary development in a 24-month-old child? Utilizing a single-subject case study design, observational sessions were conducted over four weeks, capturing the child's verbal interactions and spontaneous speech in a supportive home environment. Data analysis combined quantitative measures of new word acquisition and qualitative assessments of contextual word usage. Findings revealed a significant vocabulary spurt, with the child averaging 3.5 new words per week, characterized by peaks in word acquisition and a predominance of nouns, followed by verbs and adjectives. The child effectively utilized words for requests, labeling, and expressing emotions, demonstrating a growing understanding of syntax. Cognitive milestones, such as object permanence and categorization, alongside social influences from parent-child interactions, were pivotal in vocabulary growth. The study underscores the importance of rich, interactive environments for language development, highlighting how consistent exposure to language through routines and social engagement fosters vocabulary acquisition. These insights contribute to developmental linguistics by elucidating the cognitive and social processes that underpin early language development, emphasizing the need for supportive language-rich contexts in early childhood education.